Intermediate accounting - Spiceland, J. David (Irwin/McGraw-Hill, 2001)
This flexible text with a student-friendly writing style focuses on explaining not just how to apply a procedure, but why it is applied. It uses real-world examples to help students understand theoretical concepts and new to this edition is coverage of software revenue recognition